2013
DOI: 10.1016/j.jagp.2012.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Cognition and Amyloid Load in Alzheimer Disease Imaged With Florbetapir F 18(AV-45) Positron Emission Tomography

Abstract: Objectives We examined the association between regional brain uptake uptake of a novel amyloid PET tracer florbetapir F 18 ([18F]-AV-45) and cognitive performance in a pilot study. Design Cross-sectional comparison of florbetapir F 18 ([18F]-AV-45) in AD patients vs. controls. Setting 3 specialty memory clinics Participants 11 participants with probable Alzheimer’s disease (AD) by NINDS/ADRDA criteria and 15 healthy comparison participants (HC). Measurements Participants underwent PET imaging following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 23 publications
6
13
0
Order By: Relevance
“…Greater amyloid burden had been demonstrated to be correlated to lower cognitive performance in cognitive normal older individuals [33, 34]. The present study was consistent with the previous results and found a negative correlation between 18 F-florbetapir SUVRs and the MMSE score in the sample of all MDD patients.…”
Section: Discussionsupporting
confidence: 92%
“…Greater amyloid burden had been demonstrated to be correlated to lower cognitive performance in cognitive normal older individuals [33, 34]. The present study was consistent with the previous results and found a negative correlation between 18 F-florbetapir SUVRs and the MMSE score in the sample of all MDD patients.…”
Section: Discussionsupporting
confidence: 92%
“…Key to demonstrating this was the reliable assessment of the neuritic plaque burden through multiple regional assessments that considerably improved upon a single point CERAD assessment, which is vulnerable to sampling bias and inter-reader variability [1]. Additionally, rather than limiting histopathological or PET analysis to the 3 anatomic regions originally recommended by CERAD, global cerebral tracer retention, which is reflective of global cerebral β-amyloid deposition, is validated by the good efficacy of multiple trials and tracers [11, 12, 28, 31, 3538, 47, 5052, 6567]. Indeed, interpretation of PET images may be enhanced by the inclusion of medial cerebral gyri, notably the cingulate and precuneus, regions that have not previously formed part of the standard neuropathology assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Results of recent studies using PET β-amyloid tracers have shown a good association between tracer retention and underlying β-amyloid plaques in brain autopsy and biopsy samples [11, 12, 28, 31, 3538, 47, 5052, 6567]. However, many of these studies have drawn on a pool of end-of-life subjects with advanced disease, in which autopsy is anticipated shortly after PET imaging and with the specific goal to demonstrate efficacy.…”
Section: Introductionmentioning
confidence: 99%
“… 6 Until recently, florbetapir PET has been considered to be a valid clinical tool in the diagnosis of AD. 7 Rosenberg et al 8 reported significant inverse correlations between verbal fluency score with precuneus florbetapir SUVr. However, it is not known whether cognitive relationships exist in other DMN hubs and how they are linked with changes in regional GM volume.…”
Section: Introductionmentioning
confidence: 98%